2006
DOI: 10.1128/jvi.80.8.4122-4134.2006
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nsP3-Specific Protein Complexes during Sindbis Virus Replication

Abstract: Alphaviruses are arthropod-borne viruses (arboviruses) that include a number of important human and animal pathogens. Their replication proceeds in the cytoplasm of infected cells and does not directly depend on nuclei. Alphaviruses encode only four nonstructural proteins that are required for the replication of viral genome and transcription of the subgenomic RNA. However, the replicative enzyme complexes (RCs) appear to include cellular proteins and assemble on cellular organelles. We have developed a set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
178
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(190 citation statements)
references
References 60 publications
11
178
1
Order By: Relevance
“…However, in the last few years, our understanding of the alphavirus RNA replication mechanism has undergone some modifications. It was demonstrated that for some of the alphaviruses, such as SINV and VEEV, replication complexes are formed at the plasma membrane, and a major fraction of them remain there, even at later stages of the infection and continue to function as sites of viral RNA synthesis (49)(50)(51). Thus, RNA replication and its packaging into virions are likely to be more closely compartmentalized than we previously thought.…”
Section: Discussionmentioning
confidence: 92%
“…However, in the last few years, our understanding of the alphavirus RNA replication mechanism has undergone some modifications. It was demonstrated that for some of the alphaviruses, such as SINV and VEEV, replication complexes are formed at the plasma membrane, and a major fraction of them remain there, even at later stages of the infection and continue to function as sites of viral RNA synthesis (49)(50)(51). Thus, RNA replication and its packaging into virions are likely to be more closely compartmentalized than we previously thought.…”
Section: Discussionmentioning
confidence: 92%
“…In support of this idea, mass spectroscopy analyses of immunoprecipitated proteins from SINV-infected Rat-1 and BHK cells have identified time-dependent nsP3-associated recruitment of a variety of cellular proteins (Cristea et al, 2006;Frolova et al, 2006). These host proteins include Ras GTPase-activating protein SH3 domain-binding proteins (G3BP1 and G3BP2), 14-3-3 and heterogeneous nuclear ribonucleoproteins.…”
Section: Discussionmentioning
confidence: 92%
“…As other cellular proteins are recruited to SINV replication complexes (Cristea et al, 2006;Despres et al, 1995;Frolova et al, 2006;Gorchakov et al, 2008), PARP-1 might interact with these proteins and activate or inhibit them to promote SINV replication. It is also possible that PARP-1 is involved in stabilizing SINV replication complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Figure 3a shows the design and construction of the RC vector with an integrated thymidine kinase gene isolated from herpes simplex virus (hsvtk) gene fusion at aa 389 of the nsp3 protein (RC-Sindbis/Nsp3-tk/Fluc). We first tested whether the vector proliferation can be controlled by systemic administration of the prodrug ganciclovir (GCV).…”
Section: Resultsmentioning
confidence: 99%